The Acquisitions of the Chinese State-Owned Enterprises under the National Merger Control Regimes of the EU Member States: Searching for a Coherent Approach - Alexandr Svetlicinii (Market and Competition Law Review)
With the rapidly unfolding China’s Belt and Road Initiative (BRI ) and the ongoing reform of the State-owned enterprises (SOEs), the number of overseas acquisitions by the Chinese SOEs in various industrial and services sectors is gradually on the rise. These transactions have raised a number of questions in terms of the assessment of the economic concentrations’ potential impact on competition and challenged the traditional assessment tools employed by the merger control regimes. The paper examines the evolving experience of Chinese SOEs’ acquisitions in the European Union (EU), which are subject to ex ante assessment under both EU and national merger control regimes. The analysis of the merger assessment practice of the EU Commission culminating in the recent conditional approval of the ChemChina/Syngenta merger indicates that the traditional assessment tools, when applied to the acquisitions by Chinese SOEs, may no longer be adequate to grasp the essence of their corporate governance and decision-making. The review of the merger control practice of the national competition authorities (NCAs) also demonstrates the absence of a coherent assessment approach to the cases involving Chinese SOEs, which may lead to the inconsistent enforcement and strengthening of the foreign investment screening on grounds other than market competition.